Development of LC-MS/MS method for the determination of glutamine and GABA in CSF — case study on Alzheimer's disease patients - Muñoz, Erika Jahaira Góngora (2021)
Dissertação de Mestrado em Química Forense apresentada à Faculdade de Ciências e Tecnologia